ANALISIS SEMANGAT KERJA APARATUR SIPIL NEGARA (ASN) DI LINGKUNGAN BADAN KEPEGAWAIAN DAERAH KABUPATEN KUTAI TIMUR - Nurita Purnama Sari (ADMINISTRASI PUBLIK, 2017)
This study aims to find and describe the Spirit of State Civil Apparatus Work (ASN) in the Regional Personnel Agency of East Kutai Regency. The approach used in this research is qualitative descriptive approach. In this research will be a description of four indicators, namely Challenging Jobs, Working Conditions, Awards and Relationships With Colleagues.The results showed that the State Civil Servant Employee Spirit Level (ASN) in the Regional Personnel Officer Region of East Kutai Regency got a score of 71.4% and this included in the category is quite good. Thus the formulation of problems and hypotheses in this study have been answered and proven well.